Kebijakan Peraturan OJK Terhadap Perbankan Syariah dalam Menghadapi Wabah Covid-19 di Era New Normal - Fauzi, Inna; Anjani, Yassirlana (Sharia Faculty Islamic Economic Law Study Department, 2021)
This study aims to examine the policy of Islamic banking law in maintaining its existence in the face of the plague that is hitting Indonesia. OJK (Financial Services Authority) has also made a number of policies that are used as an effort to save the economy in Indonesia. One of the regulations is stated in POJK Number 18 / POJK.03 / 2020 concerning